Proses Inovasi Pembelajaran Kurikulum Merdeka di MTs Raudhatul Iman Tebo Jambi - Hasanah, Uswatun; Zalnur, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
In implementing innovative learning methods as part of the Merdeka Curriculum, teacher readiness and competence are key factors affecting successful implementation, with the main challenge being limited training and technical skills. The purpose of this study was to determine Learning Innovation in the Implementation of the Merdeka Curriculum at MTs Raudhatul Iman Tebo Jambi. Descriptive Qualitative research method. Research results Inadequate infrastructure and the digital divide among students are also significant barriers. In addition, the involvement of students and parents in the learning process still needs to be improved, given the importance of their support in creating a conducive learning environment. Conclusion With a strong commitment and the right strategy, MTs Raudhatul Iman can overcome the barriers and successfully implement Merdeka Curriculum effectively, improve the quality of education, and make a positive contribution to the development of education.